Exploring the second chorus in vocal jazz: a study of Sarah Vaughan’s melodic variation - Elena Mîndru (Trio)
This article explores the characteristics of the second exposition of the melody in vocal jazz performances that use the same lyrics, referred to here as the second chorus. This practice is a crucial element in vocal jazz, which allows singers to explore and experiment with their vocal delivery and to showcase their interpretative and variational skills. A case study analysing the interpretative approaches of legendary singer Sarah Vaughan is included in this article. Selected recorded tracks from Vaughan’s album Live at Mister Kelly’s were transcribed and analysed, comparing them with the original published lead sheets. The musical analysis focuses on Vaughan’s interpretation of the melody and the variations she employs during the second chorus. Her mastery of this practice, through rhythmic and melodic variations, interplay with the band, and expressive use of lyrics, enhances the musical narrative and captivates the audience. The main research question is: What musical gestures and tools does Sarah Vaughan use in her recapitulation of the melody in the second chorus of jazz songs?